2021
DOI: 10.1038/s41598-020-79391-y
|View full text |Cite
|
Sign up to set email alerts
|

Topological data analysis (TDA) enhances bispectral EEG (BSEEG) algorithm for detection of delirium

Abstract: Current methods for screening and detecting delirium are not practical in clinical settings. We previously showed that a simplified EEG with bispectral electroencephalography (BSEEG) algorithm can detect delirium in elderly inpatients. In this study, we performed a post-hoc BSEEG data analysis using larger sample size and performed topological data analysis to improve the BSEEG method. Data from 274 subjects included in the previous study were analyzed as a 1st cohort. Subjects were enrolled at the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Our previous studies showed that the BSEEG approach can detect delirium subjects 13 , 15 , 16 and predict poor outcomes 14 . It has also been shown that increased BSEEG score was observed in lipopolysaccharides-induced delirium mouse model 23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies showed that the BSEEG approach can detect delirium subjects 13 , 15 , 16 and predict poor outcomes 14 . It has also been shown that increased BSEEG score was observed in lipopolysaccharides-induced delirium mouse model 23 .…”
Section: Discussionmentioning
confidence: 99%
“…We collected raw EEG data and calculated BSEEG score as previously described 13 15 . Briefly, EEG was collected using a portable, handheld EEG device (CMS2100, CONTEC, Qinhuangdao, Hebei, China) up to twice daily during the daytime.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 , 7 We previously developed a method to detect delirium by using the bispectral electroencephalography (BSEEG) score. 7 , 8 Higher BSEEG scores were associated with higher mortality independent of delirium status. 9 In fact, we showed that BSEEG score can predict mortality of elderly inpatients better than clinical categorization of delirium.…”
Section: Introductionmentioning
confidence: 95%